On-chip sub-terahertz surface plasmon polariton transmission lines in CMOS - Liang, Yuan (2015)
A low-loss and low-crosstalk surface-wave transmission line (T-line) is demonstrated at sub-THz in CMOS. By introducing periodical sub-wavelength structures onto the metal transmission line, surface plasmon polaritons (SPP) are excited and propagate signals via a strongly localized surface wave. Two coupled SPP T-lines and two quasi-TEM T-lines are both fabricated on-chip, each with a separation distance of 2.4 μm using standard 65 nm CMOS technology. Measurement results show that the SPP T-lines achieve wideband reflection coefficient lower than −14 dB and crosstalk ratio better than −24 dB, which is 19 dB lower on average than the traditional T-lines from 220 GHz to 325 GHz. The demonstrated compact and wideband SPP T-lines have shown great potential for future realization of highly dense on-chip sub-THz communications in CMOS.